GEJOG LESUNG SANGGAR SANGIR MEMANFAATKAN KISAH MASA LALU DAN MASA KINI DARI SANGIRAN - Wiwit Hermanto (SENDIKRAF Jurnal Pendidikan Seni dan Industri Kreatif, 2023)
The aim of this study is to introduce gejog lesung by Sanggar Sangir at the Sangiran Site. Theresults of the study revealed that; (1) The studio was founded in 2015 with the initiation of theRuang Theater community and the agreement of several residents of Ngampon, Krikilan Village,Kalijambe District, Sragen Regency, (2) Every problem that occurs in the studio is resolved usinga deliberative approach and returned to the principle of self-actualization through the art of gejoglesung in free time, (3) Work in the form of songs sung other than those which are commonlyknown to the public as well as their own work as a creative effort to make the performance uniqueby combining stories from the past and daily life in Sangiran, (4) The uniqueness of the workmakes Sanggar Sangir's gejog lesung receive invitations to perform both in the surrounding areaand outside the city, and (5) Sanggar Sangir's seriousness in developing gejog lesung receivedfacilitation from the Sangiran Ancient Human Museum in 2017 and 2018 in the form of developingknowledge and improving art quality. Tujuan dari kajian ini adalah mengenalkan gejog lesung Sanggar Sangir yang ada di di SitusSangiran. Hasil kajian mengungkapkan bahwa; (1) Awal berdiri sanggar adalah tahun 2015 atasinisiasi komunitas Teater Ruang dan kesepakatan beberapa warga Dusun Ngampon, DesaKrikilan, Kecamatan Kalijambe, Kabupaten Sragen, (2) Setiap permasalahan yang terjadi di dalamsanggar diselesaikan dengan pendekatan musyawarah dan dikembalikan pada prinsip aktualisasidiri melalui seni gejog lesung dengan memanfaatkan waktu luang, (3) Karya berupa lagu yangdibawakan selain yang sudah umum dikenal masyarakat juga karya sendiri sebagai upaya kreatifuntuk membuat pementasan menjadi khas melalui pemaduan kisah masa lalu dan kehidupansehari-hari di Sangiran, (4) Kekhasan karya menjadikan seni gejog lesung Sanggar Sangirmendapatkan undangan pentas baik di wilayah sekitar maupun luar kota, dan (5) KeseriusanSanggar Sangir dalam mengembangkan seni gejog lesung mendapatkan fasilitasi dari Museum